2008
DOI: 10.1158/1078-0432.ccr-07-1565
|View full text |Cite
|
Sign up to set email alerts
|

Oral Silibinin Inhibits In vivo Human Bladder Tumor Xenograft Growth Involving Down-Regulation of Survivin

Abstract: Purpose: Chemoprevention is an upcoming approach to control bladder cancer, which is one of the commonly diagnosed malignancies showing recurrence rate of 70% or even higher. Recently, we observed the in vitro efficacy of silibinin, a flavanolignan, in human bladder transitional cell papilloma RT4 cells. Here, we investigated the antitumor efficacy and associated mechanisms of silibinin in RT4 tumor xenograft. Experimental Design: RT4 tumor xenograft was implanted s.c. in athymic nude mice, and then animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 33 publications
2
45
0
1
Order By: Relevance
“…Survivin is a member of a class of inhibitors of apoptosis and seems to block apoptosis by interfering with the caspase activation pathway. Our studies have shown that silibinin down-regulates the expression of survivin in human bladder transitional-cell papilloma RT4 cells in vitro (10) and in tumor xenograft (30). In the present study, survivin was significantly less expressed in normal bladder urothelium but highly expressed in OH-BBNinduced bladder urothelium with different stages of carcinogenesis, which was strongly decreased by silymarin or silibinin treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Survivin is a member of a class of inhibitors of apoptosis and seems to block apoptosis by interfering with the caspase activation pathway. Our studies have shown that silibinin down-regulates the expression of survivin in human bladder transitional-cell papilloma RT4 cells in vitro (10) and in tumor xenograft (30). In the present study, survivin was significantly less expressed in normal bladder urothelium but highly expressed in OH-BBNinduced bladder urothelium with different stages of carcinogenesis, which was strongly decreased by silymarin or silibinin treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Likewise, silibinin-fed SCID mice injected with SN12K1 cells exhibited a reduction in tumor size (54). Consistent with these results, several studies have shown that silibinin inhibits growth as well as induces apoptosis in several urinary bladder cancer cell lines which were associated with an increase in p53 expression, downregulation of survivin, cyclin D1, ERK1/2 phosphorylation and nuclear phospho-p65, cleavage of caspases, PARP, and Cip1/p21, and mitochondrial release of cytochrome c, Omi/HtrA2, and apoptosis-inducing factor (55)(56)(57)(58)(59)(60). This silibinin-mediated inhibition was also observed in rat models of urinary bladder cancer reducing lesions (60).…”
Section: Broad Spectrum Cancer Chemopreventive Efficacy Of Silibininsupporting
confidence: 62%
“…1A). Accumulating evidence indicates that silibinin has anticancer activity in various tumor cells, including cancers of prostate (5)(6)(7)(8)(9), breast (10,11), skin (12), colon (13), lung (14), kidney (15,16), and bladder (17)(18)(19)(20). There is increasing interest in elucidating the mechanisms of action for silibinin as an effective agent for chemoprevention and chemotherapy against various types of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…RT4 (a well-differentiated papillary noninvasive tumor phenotype) cells (17,19,20). In addition, oral administration of silibinin has been reported to prevent N-butyl-N-(4-hydroxybutyl)nitrosamine (OH-BBN)-induced mouse bladder carcinogenesis (28), suggesting a value of silibinin in bladder cancer prevention and therapy.…”
Section: Introductionmentioning
confidence: 99%